The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s1807-59322005000600005
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Patients About Cataract

Abstract: OBJECTIVE: To identify in adult patients suffering from cataract the perceptions regarding the disease and its surgical treatment. MATERIALS AND METHODS: An exploratory survey was conducted among adult patients suffering from cataract and participating in a large-scale cataract management program at the University of São Paulo General Hospital in 2004. The interviews were conducted by research assistants previously trained to pose questions and record answers. RESULTS: The sample consisted of 170 men and women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
1
9
0
7
Order By: Relevance
“…14 A study with patients in the preoperative period, carried out in 2 different hospitals with different anesthesia procedures (one used sedatives before anesthesia), highlighted the fact that anesthesia-related fear was less in patients who received pre-anesthetic sedatives, as compared to the other group receiving none. Patients reported being afraid of the surgical procedure due to fear of pain during the procedure, lack of orientation in the preoperative period, and as part of each person's strategy to cope.…”
Section: Discussionmentioning
confidence: 99%
“…14 A study with patients in the preoperative period, carried out in 2 different hospitals with different anesthesia procedures (one used sedatives before anesthesia), highlighted the fact that anesthesia-related fear was less in patients who received pre-anesthetic sedatives, as compared to the other group receiving none. Patients reported being afraid of the surgical procedure due to fear of pain during the procedure, lack of orientation in the preoperative period, and as part of each person's strategy to cope.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed at a university hospital emergency (24) , it was found that 29.4% of the patients use homemade products as the first management for the treatment of ocular diseases. Information about what people know and do regarding ocular problems is an important data for prevention and educational health programs (25) . The post-visit should stimulate the adoptions of correct managements before appeals.…”
Section: Post-visit At Ophthalmology Emergency Service: Frequency Andmentioning
confidence: 99%
“…(18) Death as a cause of fear in cataract surgery among Brazilian patients has been reported in previous studies. (15,17,19,20) Fear related to anesthesia has been reported by several studies in several kinds of surgery. (3,(21)(22)(23) In cataract surgery data were found that the most stressful facts for patients undergo surgery is the anesthesia than the surgery itself.…”
Section: Opinion Pmentioning
confidence: 99%
“…The requirement of having indication for cataract surgery by itself is cited in several studies as a important cause of fear. (4,(15)(16)(17) A study performed in Campinas (Brazil) and Chimbote (Peru) noted that 30.0% of individuals diagnosed with cataract refused surgery because of fear. (18) When analyzing the main causes of fear, it was observed that among the sensations of blindeness, worsening of vision, surgery complications, fear of anesthesia, pain, religious principles, there was no statistically significant difference between groups, suggesting that even individuals with binocular vision are afraid of losing or getting worse.…”
Section: Opinion Pmentioning
confidence: 99%
See 1 more Smart Citation